EXHIBITION PRINCIPLE IN FINE ARTS EDUCATION - Sherov Dilshod Reyimberganovich; Zaripova Yulduz Urinboy kizi (Journals Park Publishing, 2024)
This article introduces a series of methodological students to the use of visualization in visual arts education and provides information about other aspects of visualization to achieve effective results.
Keywords: fine art, the principle of visuality, didactics, nature